Statistics for process control engineers : a practical approach - King, Myke, 1951- (Wiley, 2017)
The first statistics guide focussing on practical application to process control design and maintenance Statistics for Process Control Engineers is the only guide to statistics written by and for process control professionals. It takes a wholly practical approach to the subject.